Efektifkah Fintech terhadap perkembangan pasar modal syariah? - Lailatul Qomariyyah; Febbi Dian Amalia Sari; GHIFARI ROBBY MAULANA (Journal Of Islamic Economics And Finance, 2024)
This research examines the effectiveness of the use of fintech consisting of p2p lending, equity crowdfunding, and shariah online trading system (SOTS) on the Islamic capital market. The application of fintech in the financial industry has long been implemented.  However, especially in the development of the sharia capital market, this is one potential that is quite large because Indonesia is one of the biggest muslim populations in the world. This research uses a qualitative method of literature study. This approach involves collecting analytical data from various literature sources. This research resulted in points of consideration for the effectiveness of fintech on the islamic capital market. The researcher also present challenges for the development of fintech in Indonesia that are expected to be improved for stakeholders and become suggestions for further research because fintech will continue to develop as the times change. And researcher consider that fintech is effective in the development of the capital market in Indonesia.